2011
DOI: 10.1038/jhh.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Masked hypertension in young patients after successful aortic coarctation repair: impact on left ventricular geometry and function

Abstract: Life expectancy is still reduced in aortic coarctation (AoC) patients despite a successful repair because of late arterial hypertension and atherosclerosis. Masked hypertension (MH) consists of an elevated daytime or awake ambulatory blood pressure (BP) in the presence of a normal BP on conventional measurement at the office. To assess the prevalence of MH among AoC normotensive young patients successfully treated and to evaluate the impact of MH on left ventricular (LV) geometry and function.We studied 76 AoC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 24 publications
0
27
0
4
Order By: Relevance
“…It has been shown that 24 hour BP assessment may unmask the presence of HTN which is missed with simple BP spot assessments in the clinic. Those patients with “masked HTN” have increased LV mass index and diastolic dysfunction when compared with subjects having normal BP on 24 hour assessment(20). The similarity of LV results for Corrected vs Control rabbits represents the most interesting portions of this study, suggesting correction of a 20 mmHg BPG may preserve cardiac function and LV dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 24 hour BP assessment may unmask the presence of HTN which is missed with simple BP spot assessments in the clinic. Those patients with “masked HTN” have increased LV mass index and diastolic dysfunction when compared with subjects having normal BP on 24 hour assessment(20). The similarity of LV results for Corrected vs Control rabbits represents the most interesting portions of this study, suggesting correction of a 20 mmHg BPG may preserve cardiac function and LV dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse phenomenon, masked HTN, defined as normal BP in the office setting but elevated BP outside the office occurs in approximately 10% of children and adolescents [26][27][28][29][30], although one study observed a prevalence of 38% in patients with chronic kidney disease [31]. The persistence and clinical significance of the phenomenon was analyzed in a prospective study involving 234 adolescents [28].…”
Section: Blood Pressurementioning
confidence: 98%
“…The inverse phenomenon, masked HTN, defined as normal BP in the office but elevated BP outside the office, occurs in approximately 10% of children and adolescents (74,(77)(78)(79)(80). The persistence and clinical significance of the phenomenon has shown that in 40% of children, the abnormal elevation of the daytime ambulatory BP persisted over a minimum of 6 months (79).…”
Section: White-coat and Masked Hypertensionmentioning
confidence: 99%
“…Before considering antihypertensive agents a re-coarctation must be ruled out. In children aged [7][8][9][10][11][12][13][14][15][16] years the prevalence of restenosis is suggested to be as high as 21% (276) and masked HTN is common, then ABPM should be performed regularly from the age of seven (80). Exercise HTN may also be present despite the lack of early or long-term residual or recurrent obstruction.…”
Section: Coarctation Of Aortamentioning
confidence: 99%